The Possibility of Social Conflict in the Momentum of General Elections in the Sociological Perspective of Islamic Law - Misbahuddin, Misbahuddin; Tarmizi, Tarmizi; Rahman R., Abd.; Sapa, Nasrullah Bin; Rahmawati, Rahmawati (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
The general election contest that is being held is very prone to causing conflict in society. This research aims to identify forms of social conflict, factors that cause social conflict, and the sociological perspective of Islamic law on the vulnerability of social conflict in general elections. So far, social conflict studies in general elections have mostly been studied from a social and norm perspective, but this research tries to look at the vulnerability of social conflict during general elections from the sociological perspective of Islamic law. This research is qualitative research using data obtained from online news. This research found that social conflict during general elections can take the form of arguments or debates and physical conflicts. There are at least three causes of social conflict, namely polarization or negative campaigns, selective fanaticism, and allegations of fraud. Preventing social conflict needs to be carried out using a sociological approach to Islamic law by upholding human rights, being moderate towards differences maintaining the value of balance, and being gentle. This research concludes that the sociological conception of Islamic law can be a solution to resolving social conflicts by prioritizing Islamic values. Therefore, the author suggests the need for government attention to avoid social conflict in general elections. Apart from that, support from religious figures and ulama is needed through counseling and issuing fatwas regarding the prohibition of social conflict in general elections because social conflict can damage relationships and values in society.